2003
DOI: 10.1038/nature02027
|View full text |Cite
|
Sign up to set email alerts
|

The tobacco aquaporin NtAQP1 is a membrane CO2 pore with physiological functions

Abstract: Aquaporins, found in virtually all living organisms, are membrane-intrinsic proteins that form water-permeable complexes. The mammalian aquaporin AQP1 has also shown CO2 permeability when expressed heterologously in Xenopus oocytes, although whether this is a biochemical curiosity or of physiological significance is a matter of debate. Here we report that, in the same expression system, a CO2 permeability comparable to that of the human AQP1 is observed for the tobacco plasma membrane aquaporin NtAQP1. NtAQP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
482
1
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 579 publications
(510 citation statements)
references
References 17 publications
18
482
1
9
Order By: Relevance
“…The same phenomenon was observed in tobacco plants, that is, the CO 2 assimilation rate increased in leaves over-expressing AtPIP1;2 (PIP1b) [1], or NtAQP1 [28]. Recently, we also observed increases in CO 2 assimilation in tobacco leaves over-expressing ice plant (Mesembryanthemum crystallinum) aquaporins (unpublished data).…”
Section: Aquaporins As Co 2 Transporterssupporting
confidence: 73%
See 2 more Smart Citations
“…The same phenomenon was observed in tobacco plants, that is, the CO 2 assimilation rate increased in leaves over-expressing AtPIP1;2 (PIP1b) [1], or NtAQP1 [28]. Recently, we also observed increases in CO 2 assimilation in tobacco leaves over-expressing ice plant (Mesembryanthemum crystallinum) aquaporins (unpublished data).…”
Section: Aquaporins As Co 2 Transporterssupporting
confidence: 73%
“…This was the first evidence of a direct relation between aquaporins and g i (Fig.1). Although Uehlein et al showed that membrane permeability to CO 2 increased in Xenopus oocytes expressing the tobacco aquaporin NtAQP1 [28], they did not perform the measurement of g i . Recently, Flexas et al confirmed an increase in g i of leaves of transgenic plants over-expressing NtAQP1 [7].…”
Section: Aquaporins As Co 2 Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…A dual location of some PIPs and TIPs would not be surprising taking into consideration the case of AQP1 from Nicotiana tabacum, which localized to the plasma membrane and also to the chloroplast inner envelope [33,34]. Interestingly, the substrate specificity was found to be location-dependent since only the plasma membrane AQP1 transported water, whereas the envelope AQP1 facilitated diffusion of CO 2 , although the requirement for CO 2 aquaporin in biological membranes is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…12,[38][39][40] In addition, several metabolically important small neutral solutes and ions have been identified as AQP substrates, namely hydrogen peroxide (H 2 O 2 ). 13,17,41,42 carbon dioxide, 43,44 nitric oxide, 45,46 ammonia, 47,48 metalloids such as arsenite and antimonite, 49-51 selenite, 52 boric acid, 53 and silicic acid. 51 AQP6 with low intrinsic water permeability may function primarily as an anion transporter.…”
Section: Aqp Permeability To Small Solutesmentioning
confidence: 99%